An ex vivo system to study cellular dynamics underlying mouse peri-implantation development - Ichikawa, Takafumi; Zhang, Hui Ting; Panavaite, Laura; Erzberger, Anna; Fabrèges, Dimitri; Snajder, Rene; Wolny, Adrian; Korotkevich, Ekaterina; Tsuchida-Straeten, Nobuko; Hufnagel, Lars; Kreshuk, Anna; Hiiragi, Takashi (Developmental cell, 2022)
Upon implantation, mammalian embryos undergo major morphogenesis and key developmental processes such as body axis specification and gastrulation. However, limited accessibility obscures the study of these crucial processes. Here, we develop an ex vivo Matrigel-collagen-based culture to recapitulate mouse development from E4.5 to E6.0. Our system not only recapitulates embryonic growth, axis initiation, and overall 3D architecture in 49% of the cases, but its compatibility with light-sheet microscopy also enables the study of cellular dynamics through automatic cell segmentation. We find that, upon implantation, release of the increasing tension in the polar trophectoderm is necessary for its constriction and invagination. The resulting extra-embryonic ectoderm plays a key role in growth, morphogenesis, and patterning of the neighboring epiblast, which subsequently gives rise to all embryonic tissues. This 3D ex vivo system thus offers unprecedented access to peri-implantation development for in toto monitoring, measurement, and spatiotemporally controlled perturbation, revealing a mechano-chemical interplay between extra-embryonic and embryonic tissues.